2016
DOI: 10.1108/jsbed-09-2015-0132
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation and firm performance in different environmental settings

Abstract: Purpose – The purpose of this paper is to explore the relationship between entrepreneurial orientation (EO) and firm performance across different levels of environmental hostility and market growth. The contingency approach of two-way interactions of EO with each environmental variable is contrasted with the configurational approach of three-way interactions of EO simultaneously with different levels of both environmental variables. Design/methodology/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
0
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(143 citation statements)
references
References 105 publications
6
120
0
17
Order By: Relevance
“…In line with Su, Guo, and Sun (), we used Porter's competitive strategy measures as a proxy for assessing SCA. Furthermore, although the measurement of FP by either objective or subjective measures is a challenge for researchers, prior studies have recommended self‐reported measures for FP in cases involving SMEs (Shirokova, Bogatyreva, Beliaeva, & Puffer, ). We thus relied on self‐reported measurements used by (Stam & Elfring, ; see Appendix for details).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with Su, Guo, and Sun (), we used Porter's competitive strategy measures as a proxy for assessing SCA. Furthermore, although the measurement of FP by either objective or subjective measures is a challenge for researchers, prior studies have recommended self‐reported measures for FP in cases involving SMEs (Shirokova, Bogatyreva, Beliaeva, & Puffer, ). We thus relied on self‐reported measurements used by (Stam & Elfring, ; see Appendix for details).…”
Section: Methodsmentioning
confidence: 99%
“…We thus relied on self‐reported measurements used by (Stam & Elfring, ; see Appendix for details). Likewise, we used the age and size of firm as a control variable to reduce spuriousness in the results (Shirokova et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…В то же время данная связь не универсальна для всех фирм и условий внешней среды [Широкова, Бо гатырева, Беляева, 2015;Laukkanen et al, 2013;Liu, Li, Xue, 2011;Shirokova et al, 2016]. В ра-ботах, изучающих комбинации и совмест-ные эффекты стратегических ориентаций, было обнаружено, что наилучшим резуль-татам деятельности фирмы способствует развитие сразу нескольких стратегических ориентаций, объясняемое свойством их вза-имодополняемости [Atuahene-Gima, Ko, 2001;Deutscher et al, 2016;Ho, Plewa, Lu, 2016;Lonial, Carter, 2015].…”
Section: Jel: L20 L25 L26unclassified
“…Similarly Dai et al (2014) show that the dimensions in EO have differential roles in entering new international markets. Furthermore, the ability of a firm's EO dimensions to predict its success depends on several contingencies, for example, external variables such as cultural and industry characteristics and internal variables such as organizational structure (Lomberg et al, 2016;Saeed et al, 2014;Shirokova et al, 2016).…”
Section: Eo Dimensions and Firm Performancementioning
confidence: 99%